Two Top-Down Approaches of the Public Policy: Similarities, Differences and Ethics of the Bardachâ€™s and Kingdonâ€™s Perspectives of Policy Process - ÅžimÅŸek, YÄ±lmaz (Richtmann Publishing, 2012)
This comparative review analyzes two top-down approaches of public policy, the approach of Eugene Bardach,representative of the classical side, and the approach of John Kingdon, representative the modern side. By this review, readersare going to identify and evaluate the similarities, differences and the ethics of the perspectives. This analysis shows theidentical differences about â€œhow ideas become policy.â€ This comparative review also shows the different aspects of the two topdownapproaches, so it can be also seen as a comparison of two top-down approaches of the public policy